ANALISIS PENGENDALIAN KUALITAS PADA PROSES BONING SAPI WAGYU MENGGUNAKAN STATISTICAL QUALITY CONTROL (SQC) DI PT. SANTOSA AGRINDO - Hendrawan, Dandi; Wirawati, Sri Mukti; Wijaya, Hartadi (AGUSPATI Research Institute, 2020)
PT. Santosa Agrindo (Abattoir), Kab.Serang-Gunung Kupak, Banten is a company engaged in the supply of processed meat products and beef fattening. One of the products is Wagyu beef which has been boned. This study aims to find the causes of product discrepancies and determine whether the non-conformities that occur are still within control limits or out of control using the Statistical Quality Control (SQC) method. According to the results of the P control chart graph, none of the 12 points is outside the upper or lower control limits. So there is no need for further analysis because everything is still within control limits. Meanwhile, from the results of the Pareto diagram it is known that the most dominant mismatches are 2 (two), namely the findings of feathers and lost vacum with a percentage of hair findings of 65.4% and lost vacum of 28.1%. And based on the highest percentage of mismatches, an analysis was carried out using a cause and effect diagram (fishbone) and it was found that there were several factors causing the mismatch, namely human factors inaccuracy, machine factors, namely old machine age and lack of maintenance, raw material factors, namely raw materials. which has been damaged before use and the method factor, namely the cleaning and trimming process that is not suitable